Animal Biotechnology Roles in Livestock Production. Issue 1 (March 2020) - Funahashi, Hiroaki
Abstract: Currently, meat and milk productions are significantly increasing especially in Asia. The supply of these products is vital to people's health and well-being, whereas the efficiency of beef production appears to be still lower than other meat productions. Improvements in the quality and functionality of their livestock products, as well as their production efficiency, are required for further production. Animal biotechnologies have contributed to genetic improvement, genetic diversity maintenance of domestic animals, etc. Basic animal biotechnologies, such as artificial insemination and embryo transfer, have been well established and applied as powerful tools for genetic improvement of livestock. In the applications of artificial insemination techniques, the use of sexed semen has been now widely spread, and also efforts are also made in the development of the technology using a small amount of sperm. For embryo transfer, several types of vitrification technologies have been applied to improve pregnancy rates and contributed to the international/domestic supply of livestock embryos. Conventional animal biotechnologies, such as in vitro fertilization and intracellular sperm injection, have been applied to not only livestock production and also human-assisted reproductive medicine. For in-vitro production of embryos in domestic animals, currently, oocytes have been collected from medium or large follicles (3-6 mm or larger in diameter) of ovaries. Although the oocytes derived from small follicles (less than 3 mm in diameter) exist more on the surface of ovaries, the developmental competence of the oocytes has been known to be significantly lower than those from medium follicles. If we could improve the competence of oocytes derived from small follicles significantly, we may be able to increase the number of female gamete resources for in vitro embryo production. Also, the development of techniques for producing transgenic and cloned animals has greatly contributed to the creation of pharmaceuticals and organs for xenotransplantation. Recently, furthermore, genome editing technologies, such as combined use of CRISPR/Cas9 and PiggyBac, have been developed and have made it possible to correct specific parts of the genome and introduce mutations by homologous recombination. In this review, I would like to discuss the application and progress of the above biotechnologies, including our recent research results.